To solve the given linear-quadratic system using the elimination method, we have the following equations:
- \( y = x^2 - 2x - 2 \) (quadratic equation)
- \( y = 2x - 6 \) (linear equation)
We can eliminate \( y \) by setting the two equations equal to each other:
\[ x^2 - 2x - 2 = 2x - 6 \]
Next, we will rearrange this equation to set it to zero:
- Move \( 2x \) and \( -6 \) to the left side:
\[ x^2 - 2x - 2 - 2x + 6 = 0 \]
- Combine like terms:
\[ x^2 - 4x + 4 = 0 \]
Now, we can factor the quadratic equation:
\[ (x - 2)^2 = 0 \]
This gives us:
\[ x - 2 = 0 \implies x = 2 \]
Next, we can substitute back to find the corresponding \( y \) value. We can use the linear equation \( y = 2x - 6 \):
\[ y = 2(2) - 6 = 4 - 6 = -2 \]
Thus, the solution to the system of equations is \( (x, y) = (2, -2) \).
To summarize, the final solution is:
\[ \boxed{(2, -2)} \]